LAND SUITABILITY ASSESSMENT OF JENGKOL (Archidendron sp.) & PETAI (Parkia sp.) AT WAJO DISTRICT, SOUTH SULAWESI PROVINCE - Ari WB Raharjo (Universitas Muhammadiyah Jember, 2019)
Jengkol and petai are important horticultural crops for the community. In certain seasons, the price of these commodies reach very high. The largest production area are located in Sumatra and Java. Whereas Sulawesi and Eastern Indonesia are relatively few. This study aims to analyze the suitability of land in Sulawesi (Wajo Regency) for jengkol and petai plants. This research used a field survey and laboratory analysis of 2 soil samples (mini pits) in the North and South areas. The parameters measured are temperature, rainfall, humidity, drainage, texture, rough material, soil depth, peat thickness depth, Cation Exchange Capacity, base saturation, pH, C-organic, salinity, alkalinity, sulfidic depth, slope, erosion hazard, inundation, surface materials and rock outcrops. The conclusion of this study shows that the land in Lempong Village, Bola Subdistrict has Marginal (S3) land suitability with texture and soil depth limiting factors.